A Low‐Speed, High‐Torque Motor Drive Using a Modular Multilevel Cascade Converter Based on Triple‐Star Bridge Cells (MMCC‐TSBC). Issue 4 (March 2017) - KAWAMURA, WATARU; HAGIWARA, MAKOTO; AKAGI, HIROFUMI
SUMMARY: This paper provides an experiment‐based discussion on a modular multilevel cascade converter based on triple‐star bridge cells (MMCC‐TSBC) for a low‐speed high‐torque motor drive. The TSBC is a direct ac‐to‐ac power converter capable of achieving bidirectional power flow as well as drawing and feeding three‐phase sinusoidal input (supply‐side) and output (motor‐side) currents with any power factor at both sides. This paper discusses active dc‐capacitor‐voltage control applied to the low‐speed, high‐torque motor drive. A specially designed downscaled system combining a 320‐V, 38‐Hz, 6‐pole, 15‐kW induction motor with a 400‐V, 15‐kW TSBC is constructed and tested to confirm the validity of the motor drive. Experimental waveforms obtained from the downscaled system confirm stable operation with the rated load torque across a range from a standstill to the rated speed, including satisfactory start‐up performance.